2003
DOI: 10.1097/01.ccm.0000050298.59549.4a
|View full text |Cite
|
Sign up to set email alerts
|

Empirical antimicrobial therapy of septic shock patients: Adequacy and impact on the outcome*

Abstract: The prescription of empirical antimicrobial therapy by a senior physician in agreement with practice guidelines made it possible to achieve a crude rate of 89% of adequate antimicrobial therapy in study patients. Inadequate antimicrobial therapy was associated with a 39% excess of mortality. A de-escalation of the empirical therapy was possible in 64% of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
92
1
5

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(103 citation statements)
references
References 29 publications
5
92
1
5
Order By: Relevance
“…In agreement with observational studies [3], our trial in patients with severe sepsis showed that de-escalation did not affect mortality. In contrast, de-escalation was associated with an increased use of antimicrobials.…”
supporting
confidence: 91%
“…In agreement with observational studies [3], our trial in patients with severe sepsis showed that de-escalation did not affect mortality. In contrast, de-escalation was associated with an increased use of antimicrobials.…”
supporting
confidence: 91%
“…This in turn could reduce the overall mortality among patients with gram negative bacteraemia as has been documented in previous studies. 10 FISH has proven to be a powerful molecular method for identiÞ cation, visualization and quantiÞ cation of organisms of interest in microbial communities. 11 Several reports show that FISH has already been successfully applied for the detection of E. coli, H. pylori, Staphylococcus aureus and Brucella spp.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, tailoring antibiotic therapy to the organism sensitivity data results in lower mortality (B) (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)21,22,(24)(25)(26) (D). (17)(18)(19)(20) Some studies have shown that running blood cultures in patients without risk factors hospitalized for community-acquired pneumonia may not be costeffective given the low rate of positive results (B) (31) (C) (32) .…”
Section: Recommendationmentioning
confidence: 99%
“…The earlier appropriate therapy is started, the better the patient's prognosis will be (B). (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) Appropriate antibiotic therapy allows for deescalation from empirical therapy to a more specific antibiotic regimen, which is suitable for organism sensitivity and may prevent the risk of selecting resistant bacteria (D). (17)(18)(19)(20) Antibiotic de-escalation to more specific and less numerous antibiotic regimens reduces the overall cost of therapy (B).…”
Section: Is the Causative Agent Identification Relevant?mentioning
confidence: 99%